Paradoxes of populism : troubles of the West and nationalism's second coming - Hedetoft, Ulf (Anthem series in citizenship and national identities., 2020)
Populism may come across as little more than an extreme form of national belonging--nationalism run wild so to speak--a case for national psychologists or a kind of collective pathology. However, as so often, appearances are deceptive. "Paradoxes of Populism" argues that the far-from-random similarities with ordinary manifestations of nationalism should be approached not as a venture into the classical structures of nation-states and identities, but as a disruptive and destabilizing consequence of some of the constituent elements of sovereign nation-states becoming eroded and prised apart by contextual global processes and their agents. This book sets out to engage with these real-world challenges as well as their political and cultural interpretations in the populist fantasia